Teaching as a Political Act: Critical Pedagogy in Library Instruction - Melia Erin Fritch (Educational Considerations, 2018)
This article establishes a theoretical framework for critical library instruction (and thereby critical information literacy) that is built upon critical feminist theory, critical race theory, and engaged pedagogy, among others. Using the ideas and work of theorists to create a path linking the ideas of critical analyses together, the author demonstrates the importance and need for critical information literacy within library instruction to empower students, creating opportunities for lifelong learning. Noted within the article are the obstacles for librarians who focus on feminist engaged pedagogy in their teaching; however, the author shares with readers that the challenge is in fact worth the struggle. Overall, the article presents a theoretical foundation for the author’s call to action – it’s time for librarians to move forward as teachers-as-activists roles and use library instruction as a transformation into a lifelong learning experience for students.
Keywords: critical library instruction; critical feminist theory; engaged pedagogy; critical information literacy; critical race theory